Networking System Employing near Infrared Spectroscopy for Sugarcane Payment in Japan. Issue 6 (December 2013) - Taira, Eizo; Ueno, Masami; Furukawa, Noboru; Tasaki, Atsuya; Komaki, Yuzo; Nagai, Jun-Ichi; Saengprachatanarug, Khwantri
A cane quality evaluation system using near infrared (NIR) spectroscopy for determining payments to growers was developed and introduced to raw sugar mills in southern Japan. The evaluation system consists of a cutter grinder for sample preparation, an NIR instrument and a networking system. We investigated a calibration model for the determination of sugar index [Pol in cane, (PIC)] for shredded cane samples using a modified partial least squares regression with and without a repeatability file. The accuracy of the model developed using the repeatability file was adequate [root-mean square error of prediction, ( RMSEP ) = 0.30%] and the pooled standard error ( P-SE ) between master and eight slave instruments was 0.14%. In contrast, calibration models without a repeat ability file incurred large P-SE and pooled bias ( P -bias) values, although the RMSEP values were very similar to the repeatability file model in cases using the first derivative and standard normal variate (SNV) spectral pre-treatment. The evaluation system was installed in 17 raw sugar mills on 13 islands involved in sugarcane cultivation in southern Japan. The system is presently used to measure the PIC value of cane samples that are supplied by farmers to mills. All data obtained are collected and compiled into a central facility via the Internet. The NIR networking system for sugarcane has been implemented in all raw sugar factories in Japan as an official method for determining cane prices.